Respostas

2013-12-05T09:14:35-02:00
X=3-y    x=9+y   3-y=9+y  y+y=3-9    2y=-6  y=-6/2   y= -3    x=3-y    x=3-(-3)   x=3+3  x=6 X=6 Y= -3
2013-12-05T09:15:55-02:00
X+y=3                                                                                                                                                x-y=9                                                                                                                                                x+x+y-y=3+9                                                                                                                                    2x=12                                                                                                                                                x=12/2                                                                                                                                                x=6                                
1 5 1